Peran Peningkatan Data dan Review Sistem Informasi Sumber Daya Air Indonesia untuk PPSI Daerah Irigasi Kewenangan Pusat (Water Resources Data Center Versi 1.0) - Tommy Kurniawan; Ari Setyorini; Dian Kamila; Gandes Sawitri; Tri Handoko; Laode Muhamad Bakti; Hadijah Usman; Andi Sudirman; Adi Nuryono (Universitas Siliwangi, 2024)
The Sustainable Development Goals are the UN's 2015 goals as a guide for all member countries to achieve sustainable development, with a score of 48 (medium low) in 2017 and a score of 66 in 2020 (medium high). Indicator 6.5.1 is the degree of indicator for the implementation of Integrated Water Resources Management (IWRM) in Indonesia. Currently, demands for the application of Information and Communication Technology in natural resource management are increasing, including: installation of sensors for monitoring and real time data acquisition, telemetry data transmission, water management decision support systems, spatial data visualization, and infrastructure operation with teleoperation systems. There are problems with incomplete, unsynchronized data, duplicate data and overlaps in data management. This study was conducted to 1) determine the role of Indonesian SDA SI on PPSI and IWRM, 2) standardize data, 3) inventory IS to support SDA I, and 4) assess SDA I. The research and development methodology in this study refers to reviewing and development the product. The results of the study show that the government's efforts to increase the IWRM indicator value according to indicator targets and manage natural resource conflicts are in line with PPSI. This is an effort to manage data for policy, availability of Integrated Natural Resources data and information that is valid. Data standardization needs to be carried out because SI in the Ministry has different characteristics. This information system has been identified and prepared for development based on the SDA I evaluation, namely data grouping, spatial presentation, tabulation and visualization.